Avalia????o de um modelo colaborativo suportado por tecnologias da web 2.0 para apoiar a gest??o de li????es aprendidas em projetos de seguran??a patrimonial usando uma abordagem de design science - Souza, Maur??cio Tessi de (2016)
Social software, eg Wikis, Blogs and Microblogs, have gained attention in recent years in the daily life of organizations, these can be incorporated into the project management and collaborative tools. Regarding organizations, these tools can facilitate the sharing of lessons learned and knowledge among employees of an organization and the external public. These facilities can be seen through the real-time communication, access to information by multiple people at the same time and control of information exercised by management or organization. Moreover, the lessons learned are one of the central points of this research, which contributed directly to the organization, management and the security project teams. This study aims to evaluate to what extent the use of an artifact produced by a lessons learned management model can contribute to the management of security projects. As research question of this study narrowed to the following, "To what extent the lessons learned Target 2.0 management model can contribute to the management of security projects?" To this end, this study uses the Design Science Research as a research paradigm and the Technical Action Research as a method, which will reduce the gap between research and practice. This work is characterized as qualitative, using interviews and direct observations techniques. We used a Wiki as a central tool of this artifact, noting the facilities of inputs, consultations and control of the lessons learned from the management and design teams. The device was applied to the organization through a Web 2.0 tool, ie a Wiki, which served as support and support to project teams in the collection of lessons learned. The study found that even the use of the artifact has contributed significantly to the practice of security projects, as there was an improvement in communication between staff and management. Another point seen in the study was the ease of use of the tool users in the process. One of the limitations is the availability of Internet, which is still a problem, because without Internet, the virtual tools or social media are compromised, being a hindrance to the team's work in the field. As a contribution to the theory the artifact created can improve Lessons Learned storage and communication between property security project teams and their managers in the researched organization.